Upaya Peningkatan Minat Belajar Fisika Dengan Menggunakan Metode PhET Simulation - Lastri Manulang; Jesika Elisabeth; Jesi Alexander (Pusat Riset dan Inovasi Nasional, 2024)
Personal potential that goes through a significant process and is one of the needs that must be met is education. As educators, teachers must be smart in utilizing existing technology to develop learning media in an effort to increase effective learning. One of the problems encountered in creating learning media is practical learning on physics material. One example is creating media using Google products and the